Scientific follow-up of a high-performance team: The example of Australian water polo - Mujika, I. (First international symposium sciences and practices in swimming, 2006)
Water polo is a high intensity, intermittent team sport that requires the development of all energy/power Systems, as well as muscular strength, power, flexibility, technical and tactical skills. Players are often tested to assess fitness and performance level. In the Australian testing model, testing is performed to identify weaknesses, monitor progress, provide feedback, educate coaches and athletes, and predict performance potential. Tests are selected according to their relevance, specificity, practicality, validity and accuracy. Quality control of testing pays attention to standardising testing conditions, precision, reliability and interpretability of results. In addition to musculoskeletal screening and anthropometry, elite Australian players perform a battery of tests including and incremental aerobic swim, speed-endurance swim, sprint swims, vertical reach and dry land maximal strength and strength endurance tests. New water polo specific tests such as the Water polo Intermittent shuttle Test and the Water polo Specific Fatiguing Test have been developed and validated at the Australian Institute of Sport. These tests have been used to assess match-fitness in elite players, to determine the effects of fatigue on decision-making and shooting skill performance, and to evaluate the effects of different training and nutritional interventions on simulated water polo performance.